Azaphilic versus carbophilic coupling at C=N bonds: key steps in titanium-assisted multicomponent reactions - Roth, Torsten; Wadepohl, Hubert; Clot, Eric; Gade, Lutz H. (Chemistry - a European journal, 2015)
Abstract Consecutive C- and N-arylation of N-heterocyclic nitriles is mediated by titanium(IV) alkoxides. The carbo- and azaphilic arylation step may be separated by choosing the order in which the two equivalents of aryl transfer reagent are added. In the course of this transformation, the ancillary N-heterocycle acts as both a directing anchor group and electron reservoir. In the selectivity-determining step, the selectivity is governed by a choice between (direct) C- and Ti-arylation; the latter opens up a reaction pathway that allows further migration to the nitrogen atom. The isolation of metal-containing aggregates from the reaction mixture and computational studies gave insights into the reaction mechanism. Subsequently, a multicomponent one-pot protocol was devised to rapidly access complex quaternary carbon centers.